A Rare Case of Neonatal Complicated Appendicitis in a Child with Patau's Syndrome - Valentina Pastore; Fabio Bartoli (Hindawi Limited, 2014)
Neonatal appendicitis is a rare condition with high mortality rate. Signs and symptoms are often nonspecific, imaging modalities are not always diagnostic, and preoperative diagnosis is difficult with subsequent delay and complications. Its pathophysiology may be different from appendicitis in older children and comorbidities can be found. We report a case of a female neonate with Patau's syndrome, intestinal malrotation, and Fallot tetralogy in whom perforated appendix, probably occurring during fetal period due to vascular insufficiency, was found at laparotomy.